Hubungan Antara Pola Konsumsi Junk Food Dengan Status Gizi Atlet Petanque FIKK UNM - M. Rachmat Kasmad (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
This study aims to determine the relationship between junk food consumption patterns and nutritional status in FIKK UNM petanque athletes. The independent variable in this research is consumption of junk food, while the dependent variable is nutritional status. The type of research used is quantitative with a cross sectional approach, taking place at FIKK UNM. The population in this study were all FIKK UNM petanque athletes, while the total sample was 22 athletes. Nutritional status was obtained using the BMI/U anthropometric index, and junk food consumption using the FFQ questionnaire. The data was then analyzed using the chi square statistical test. The results of the chi square statistical test were 0.232 (p<0.05). The conclusion of this research is that there is no significant relationship between junk food consumption patterns and the nutritional status of FIKK UNM petanque athletes.